Sustainable Production of Perfluorocarbon, Ionic Liquid and Deep Eutectic Solvents based Nanoemulsions by Membrane Emulsification for Biomedical and Bioprocessing Applications - Taqui, Syed Usman (2021)
In the quest to replace toxic, volatile and harsh solvents, and to abide by the principles of green and sustainable chemistry and engineering, various functional solvents have been in-troduced in the last two decades. The synthesis of perfluorocarbons and hydrophobic ana-logues of ionic liquids (ILs) and deep eutectic solvents (DESs) are some of the examples pub-licising hydrophobic designer solvents. However, in order to potentiate bio-based applica-tions, wherein polar media is usually encountered, the low solubility of these hydrophobic solvents in water was tackled in this work by dispersing them as nanoemulsions. Membrane emulsification was introduced in the end of the last century as an energy-efficient method to produce microemulsions. In the current study, various nuances of membrane emulsification processes were re-visited and re-established for the sustainable production of nanoemulsions. For a comparative analysis, the traditional ultrasound emulsification tech-nique was employed. Perfluorodecalin-in-water nanoemulsions with enhanced stability were formulated using a 30 nm isoporous polymeric membrane by ‘direct membrane emulsifica-tion’ with reduced energy consumption. The high viscosity of ionic liquids (ILs) was ad-dressed for the first-time by ‘premix membrane emulsification’ to formulate IL-in-water nanoemulsions by using the aforementioned membrane. Subsequently, the preparation of novel PVA membranes embedded with micro/nano capsules of silica(shell)/ionic liquid (core) resulted in enhanced CO2 capture. In another case-study, the unique observation of self-as-sembly of DES enabled the formulation of hydrophobic DES-in-water nanoemulsions by iso-porous membranes with nominal pore sizes of 30 – 1000 nm. This phenomenon termed as ‘membrane-assisted nanoemulsification’ was harnessed by fabricating microengineered iso-porous metallic membranes with high physicochemical stability and reusability to formulate DES-in-water nanoemulsions. These nanoemulsions exhibited enhanced antimicrobial activ-ity and improved drug solubility for drug delivery applications. Lastly, this study reinforces the use of membrane emulsification processes as sustainable approaches to formulate cheaper and contamination-free nanoemulsions with controlled size and dispersity when compared to conventional energy-intensive emulsification techniques.